Effects of Students’ Competency in using CEHRD Learning Portal and Technology integration in Mathematics on Academic Performance - Joshi, Dirgha Raj; Sharma Chapai, Krishna Prasad; Khanal, Bishnu (International Research Journal of MMC, 2025)
The aim of this research was to examine how different aspects of technology use, including students’ competency in using CEHRD learning portal, types of activities, content areas, and time spent using devices, affect their performance in mathematics. This study employed a cross-sectional survey design within a quantitative framework, involving a sample of 704 students from 13 schools in the Kathmandu district of Nepal using stratified random sampling technique. Data were collected using questionnaire and analyzed using frequency, percentage, ANOVA, and path analysis to examine the effects of various aspects of technology use on students’ mathematics achievement. Findings indicates that the students with higher competency in using the CEHRD learning portal performed significantly better in mathematics, with highly competent students achieving the highest scores. However, there was no significant difference in achievement based on the type of technology use for learning activities or the mathematical content most frequently studied, though some positive trends were noted in areas like Algebra and learning new mathematical knowledge. Additionally, students who used mobile phones and laptops for less than one hour showed better performance than those who used them for longer periods or not at all, suggesting that moderate use of technology may be more effective for learning mathematics.